Travel demand management: short review of the special issue - Ge, Ying-En; Tang, Chunyan; Prentkovskis, Olegas; Saleh, Wafaa; Junevičius, Raimundas; Bell, Michael G. H. (Transport, 2014)
"Travel demand management: short review of the special issue" Transport, 29(3), pp. 233-234 First Published Online: 22 Sep 2014